Comparison of staple closure of skin versus suture closure of skin in elective surgical wounds - Chavali, Pravalika; Ganta, Nithya; Reddy, M. Mallikarjuna (International Surgery Journal, 2025)
Background: The development of surgical skills and the handling of instruments have led to an understanding of operative procedures. Emergency surgeries and insertion of foreign bodies are done when one deals with acute sepsis adhesive and staples are used instead of sutures. The principle idea is to regain the wound's strength as quickly as possible with the most minor tissue damage and an acceptable cosmetic scar. The critical step is the accurate co-optation of dermal edges. The skin closure technique auto-inoculates the patient's wound, deepening surface flora into the subcutaneous layer. Methods: Patients who underwent abdominal surgeries in an elective setting in NRI Medical College hospital, Chinakakani, were included in this prospective study. Patients were randomly assigned to skin sutures/staplers for wound closure in elective surgeries and 50 cases were studied in either group (total–100 cases). Cases were studied from August 2022–April 2024. Results: About 16% patients who underwent staple skin closure had complications. About 82% patients who underwent suture skin closure had complications. Discharge and seroma are the most common complications in this group. The cosmetic outcome for incisions closed with staples was better than sutures. The time taken for removal of staples is significantly less compared to suture removal. The postoperative pain is more or less the same in both the groups. Conclusions: we conclude that skin staplers are superior to sutures in wound cosmesis, reducing the wound discharge/ infection, seroma formation, granuloma formation and very much significant in saving time for skin closure. With reduction in the incidence of postoperative complications, wound healing improved and gaping significantly reduced giving better cosmetic scar.